Emotive Function and Catharsis in Maxim Online Motorcycle Taxi Drivers’ Register: A Sociolinguistic Study in Palu City - Engka Ulang Rahmadani; Nayla Cahyu; Indra Indra; Reynaldy Daud (Applied Linguistics: Innovative Approaches and Emerging Trends, 2025)
This study investigates the emotive functions and cathartic effects in the language register used by Maxim online motorcycle taxi drivers in Palu City, Central Sulawesi. Using a descriptive qualitative method, data were collected through field observations, semi-structured interviews, and note-taking from three purposively selected informants. The analysis was conducted using the multidimensional register framework developed by Biber and Conrad (2009, 2019). The results show that the drivers’ registers consist of three main types: (1) adoption of digital terms (cancel, on/off, on-bid, nge-tap), (2) metaphorical extensions (gacor, anyep, paus), and (3) interference from the local Kaili language (balengga). Functionally, these registers play important roles in improving operational efficiency, providing emotional catharsis (e.g., gacor for expressing happiness and anyep for venting frustration), and constructing group identity within the driver community.